Factor Analysis Of The Use Of Vct Services In Pregnant Women At Puskesmas Rukun Lima, Ende District - Owa, Khrispina; Bai , Marieta K.S. (Sean Institute, 2022)
Background Human Immunodeficiency Virus (HIV) is a contagious infectious disease which is grouped as a factor that can affect maternal and child mortality (Ministry of Health, 2014). In 2015-2017 several cases of HIV were found in pregnant women and were transmitted to infants which resulted in infant death due to HIV infection in the working area of the Rukun Lima Health Center. The VCT program has been implemented since 2017 but of the total pregnant women who perform ANC only 50% accept to carry out examinations through VCT services. The aim of the study was to analyze the factors that influence the use of Voluntary Counseling and Testing (VCT) in pregnant women at the Rukun Health Center Five. Observational Analytical Design Method. The approach is carried out by cross sectional. Research data was collected from June to August 2020 using a questionnaire. There are 2 data analyzes carried out in this study, namely descriptive analysis used to determine the frequency distribution of each respondent. Meanwhile, to find out the relationship between the independent variable and the dependent variable, bivariate and multivariate analysis is used. The results of the univariate analysis revealed that pregnant women with less knowledge of HIV were 53.48%, supported by facilities, 58.14%, supported by service providers 65.12% and pregnant women who did not have VCT examinations were 62.79%. The results of the bivariate analysis found that there was a relationship between the knowledge and support of service providers and the participation of pregnant women in VCT examinations. Knowledge (Asymp.sig.(2-sided)= 0.000) and OR= 4.2), support for health service providers (Asymp.sig.(2-sided)= 0.000) and OR= 5.2) while facility support VCT services have a relationship with the use of VCT services in pregnant women with (Asymp.sig.(2-sided) = 0.000) and OR = 0.2), The conclusion is that the factors of mother's knowledge about HIV, staff support and support for service facilities influence the use of VCT services in pregnant women at the Rukun Lima Health Center.